Discrepancies in Physician and Coroner Findings in Cases of Fatal Suspected Physical Child Abuse. Issue 7 (July 2021) - Arnold, Tyler S.; Siekmann, Tyler; Thackeray, Jonathan D.; Bridge, Jeffrey A.; Cohen, Daniel M.
Abstract : Objectives: As mandated reporters of suspected abuse, physicians must consider abuse when a child dies unexpectedly. Subsequently, a coroner or medical examiner determines the manner of death (MOD) and cause of death (COD). Accurate diagnoses and determinations are important for social safety and justice. This study described discrepancies between physicians' and coroners' findings in cases of fatal suspected physical child abuse. Methods: This study was a single-institution, retrospective review. All children 6 years or younger who died in a pediatric emergency department from October 2006 to January 2013 with a coroner report were included in this study. Coroner reports, MODs, and CODs were reviewed. Skeletal survey results were compared with coroners' findings. Results: One hundred twenty-nine children were included. The MODs included the following: undetermined, 63 (49%); accident, 32 (25%); natural, 31 (24%); and homicide, 3 (2%). Thirty-three (26%) of the 129 patients had abuse suspected at the time of death in the emergency department; in this subset, MODs were as follows: undetermined, 16 (48%); accident, 8 (24%); natural, 6 (18%); and homicide, 3 (9%). Sudden infant death syndrome or sudden unexpected death was the most common COD in all children (68, 55%). Skeletal surveys were positive in 12 children with 29 fractures identified; 8 (28%) of the 29 fractures were corroborated on autopsy findings. Of the 12 children with positive skeletal survey findings, only 1 was ruled a homicide. Conclusions: We found discrepancies between coroner determination of homicide and abuse suspected by physicians, especially among children with fractures. Improved communication between agencies in cases of fatal child abuse is needed.